Analisis Timbulan Limbah Medis B3 Fasyankes di Kabupaten Banyuwangi pada Masa Pandemi Covid-19 Tahun 2020 - Arisma Ifatul Hanisya; Ririh Yudhastuti; Septa Indra Puspikawati (Media Gizi Kesmas, 2023)
Background: Most health service activities hospitals and health centers provide produce B3 medical waste. B3 medical waste is the residue from the results of service activities to patients containing B3 (Hazardous and Toxic Materials). The Covid-19 pandemic has an impact on increasing the amount of B3 medical waste produced by hospitals and health centers, this is because many health facilities are visited to get special treatment for patients exposed to Covid 19. The Covid-19 pandemic in Banyuwangi Regency has occurred since March 2020 and is increasing daily. This pandemic has affected the increase in medical waste produced by health facilities such as hospitals and health centers, especially in healthcare facilities that are referrals for Covid-19 patients. Objective: This study aims to analyze the generation of B3 medical waste during the Covid-19 pandemic at hospitals and health centers in Banyuwangi Regency from March to December 2020. Methods: The research method used was quantitative research and research studies using secondary data from the Banyuwangi Regency Environmental Service from March to December 2020 for analysis. This study used descriptive analysis techniques by displaying graphs and mapping the area per sub-district. Results: The results of the research that had been carried out show that the generation of B3 medical waste from hospitals in the March - December 2020 period during the pandemic was 110,268 kg, the hospital that produced the largest B3 medical waste was Blambangan Hospital (46,343 kg). The largest generation of B3 medical waste from Puskesmas occurred in July (1709 kg), while the smallest occurred in December (382 kg). The sub-districts that produce B3 medical waste in the large category are Genteng and Banyuwangi (21,241 – 31,822 kg), and the medium category is Glenmore sub-district (10,661 – 21,241 kg). Conclusion: B3 medical waste generated by hospitals is greater than B3 medical waste from health centers. This is because most hospitals are used as referral health facilities for handling Covid-19 patients. The total amount of B3 medical waste produced by hospitals is 110,268 kg, while B3 medical waste produced by puskesmas is 10,541 kg.